Targeted Metabolomics in the REasons for Geographic and Racial Differences in Stroke (REGARDS) Study - Zsuzsanna Ament; Naruchorn Kijpaisalratana; Varun M. Bhave; Catharine A. Couch; Ana-Lucia Garcia Guarniz; Amit Patki; Mary Cushman; Suzanne E. Judd; M. Ryan Irvin; W. Taylor Kimberly (Scientific Data)
Abstract Targeted metabolomics was conducted on plasma samples from a nested case-cohort study within the biracial REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. This longitudinal study investigates health outcomes with a focus on stroke disparities across the United States, particularly in the Southeastern “Stroke Belt,” where stroke risk and mortality are 2–4 times higher in the Black population. The REGARDS study recruited 30,239 Black and White participants aged 45 years or older. This dataset includes 2,377 baseline plasma samples collected between 2003 and 2007 from a stroke case-cohort sub-study, with 1,056 randomly selected cohort participants and 1,321 stroke cases. The resulting data provides a resource for investigating metabolic profiles and their potential implications for health outcomes and disparities.